Tingkat Partisipasi Masyarakat Dalam Menjaga Kelestarian Hutan Mangrove Di Cagar Alam Maubesi (Studi Kasus Desa Kletek Kecamatan Malaka Tengah Kabupaten Malaka) - Angela Yunita Kehi; Nixon Rammang; Fadlan Pramatana; Pamona Silvia Sinaga (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia is one of the archipelagic countries that possesses rich marine and coastal resources, both biological and non-biological, one of which is the mangrove forest ecosystem. One of the regencies that has a distribution of mangrove forest ecosystems in East Nusa Tenggara (NTT) is Malaka Regency, specifically in the Maubesi Mangrove Forest Nature Reserve. Theft and logging occurring in the area, particularly involving the santigi mangrove species, can damage the mangrove ecosystem. These issues arise due to the lack of government oversight and limited community participation in protecting the area. Therefore, community involvement is necessary to preserve the mangrove forest. This study aims to determine the level of community participation in Kletek Village in preserving the mangrove forest. Data collection was conducted through field observation, interviews, and documentation using a qualitative descriptive analysis method. Sampling was carried out using purposive sampling. The results of the study indicate that the participation of the Kletek Village community in preserving the mangrove forest is divided into three stages: the planning stage, the implementation stage, and the evaluation stage. The planning stage showed a moderate level of participation at 65.42%, the implementation stage showed a high level of participation at 83.75%, and the evaluation stage showed a moderate level of participation at 63.37%. Factors influencing the level of community participation in preserving the mangrove forest include the level of education, livelihood influences, and the level of public awareness.